A methodological framework with rough-entropy-ELECTRE TRI to classify failure modes for co-implementation of smart PSS. (October 2019) - Liu, Zhiwen; Ming, Xinguo
Abstract: Smart PSS (product-service system) has been transcending the scope of traditional PSS through ICTs (information and communication technologies). The co-implementation is a specific way of co-creation to generate value for customer and supplier in smart PSS. Meanwhile, the service failures in co-implementation can bring about service paradox. As such, three key research questions, including the construction of co-implementation of smart PSS, the extension of risk factors in FMECA and the category of identified failure modes, are put forward and conquered by a proposed methodological framework. First, in order to construct the co-implementation of smart PSS involving customer and supplier, the PCN (process-chain-network) diagram with direct interaction, surrogate interaction and independent handling is employed to reflect the nature of interaction. Second, since that the highly complexity of co-implementation of smart PSS can lead to more huge risk, an extended-FMECA (failure mode effect and criticality analysis) sheet is formulated by considering the adaptation of autonomy. Third, to handle the uncertainty of expert judgments more reasonably and determine the weights of risk factors without additional information, a hybrid approach integrating rough-entropy-ELECTRE TRI is proposed to classify failure modes into ordinal classes, so that decision-makers can swiftly access them. This proposed methodological framework also is illustrated by the co-implementation of smart fridge-service system, in which the feasibility and superiority are verified by analysing comparative results.